2001
DOI: 10.1099/0022-1317-50-2-135
|View full text |Cite
|
Sign up to set email alerts
|

Verocytotoxin-producing Escherichia coli (VTEC) O157 and other VTEC from human infections in England and Wales: 1995–1998

Abstract: A total of 3429 isolations of verocytotoxin-producing Escherichia coli O157 (VTEC O157) was con®rmed from human sources in England and Wales during the period 1995±1998. The largest annual total was 1087 in 1997. Most infections occurred in the third quarter of each year. The overall rate of infection ranged from 1.28 to 2.10=100 000 population and showed regional variation. The highest incidence was in children aged 1±4 years. Annually, between 5% and 11% of strains were from patients who had travelled abroad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
126
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 21 publications
8
126
0
3
Order By: Relevance
“…Verocytotoxin-producing Escherichia coli (VTEC), and particularly strains of serotype O157:H7, are recognised as a major cause of diarrhoea, bloody diarrhoea and haemolytic uraemic syndrome (HUS) in North America [1] and the UK [2]. Certain other VTEC, and in particular those belonging to serogroups O26, O103, O111 and O145 [3], also cause a disease characterised by bloody diarrhoea, which may develop into HUS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Verocytotoxin-producing Escherichia coli (VTEC), and particularly strains of serotype O157:H7, are recognised as a major cause of diarrhoea, bloody diarrhoea and haemolytic uraemic syndrome (HUS) in North America [1] and the UK [2]. Certain other VTEC, and in particular those belonging to serogroups O26, O103, O111 and O145 [3], also cause a disease characterised by bloody diarrhoea, which may develop into HUS [4].…”
Section: Introductionmentioning
confidence: 99%
“…Although some rapid PCR-based methods, such as those based on randomly amplified fragments (RAPD), or repetitive element PCR (Rep-PCR), may not give sufficient discrimination as a consequence of the highly clonal nature of VTEC O157 (Willshaw et al, 2001), we were able to find three different RAPD profiles among six strains belonging to serotype O157 : H7.…”
Section: Resultsmentioning
confidence: 79%
“…The rationale for focusing on these serogroups is due to the fact that STEC is associated with a wide spectrum of illness ranging from uncomplicated watery diarrhea to hemorrhagic colitis (HC) and hemolytic uremic syndrome (HUS), which may result in death and many studies have confirmed that serogroups O26, O103, O111, O145 and O157 are highly associated with HC and HUS. [26][27][28][29][30][31] In pure culture, the direct detection limits of the Phazyme assays ranged from 6.82 x 10 4 CFU/ml for serogroup O145 to 1.32 x 10 6 CFU/ml for serogroup O111 ( fig. 2).…”
Section: Resultsmentioning
confidence: 99%